The Relationship Between Innovative Thinking Skills of Administrators and the Effectiveness of Academic Administration in Schools Under the Secondary Educational Service Area Office, Phichit - Kronpom, Kitti; Sawangmek, Taweesak (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to 1) examine the innovative thinking skills of school administrators, 2) investigate the effectiveness of academic administration, and 3) explore the relationship between administrators' innovative thinking skills and the effectiveness of academic administration in schools under the Secondary Educational Service Area Office, Phichit. The study employed quantitative research methodology. The sample consisted of 278 teachers from schools under the Secondary Educational Service Area Office, Phichit, in the academic year 2024, selected through stratified random sampling based on Krejcie and Morgan’s sample size determination table. Data were collected using a five-point rating scale questionnaire. Statistical methods employed for data analysis included frequency, percentage, mean, standard deviation, and Pearson’s product-moment correlation coefficient. The research findings revealed that: 1) The innovative thinking skills of school administrators were rated at a high level overall and across all dimensions, including innovative awareness, thinking network, imaginative thinking, persistent practical thinking, and integrative thinking. 2) The overall effectiveness of academic administration in schools under the Secondary Educational Service Area Office, Phichit, was also rated at a high level. Specifically, the aspects of learning management supervision and media, technology, and learning resources management were rated at the highest level, while internal quality assurance, knowledge assessment and evaluation, curriculum administration, and research for development were rated at a high level. 3) There was a statistically significant positive correlation at the .01 level between the innovative thinking skills of school administrators and the effectiveness of academic administration in schools under the Secondary Educational Service Area Office, Phichit. This finding suggests that higher levels of innovative thinking among school administrators are associated with greater academic administrative effectiveness.